Project Manager Knowledge, Skill, And Competency Measurement Using Project Manager Competency Development Framework (PMCDF®) (Study Case Fronthaul Easy Macro BTS Telkomsel Project) - Lestari, Ayu Novita; Puspita, Ika Arum; Yasa, Putu (eProceedings of Engineering, 2024)
PT XYZ is a subsidiary of TelekomunikasiIndonesia, Tbk which is engaged in construction services, one ofwhich is working on an easy macro project fronthaul accordingto orders from Telkomsel. The Fronthaul Easy MacroTelkomsel BTS development project is a fiber coreinfrastructure provision service as a solution for implementingcellular networks, especially in areas that can only be reachedby micro BTS. The project is known to experience delays pastthe completion date specified in the contract. In the problemformulation, the author gives weight to the 3 largest humanresources, namely the project managers involved in the project.Measuring project manager competency by distributingquestionnaires according to the PMCDF® method, namelyaspects of the project manager's personal competency. By usingthe AHP model as weighting and measuring with a Likert scale.The results on the PMCDF reference obtained the 3rd largestweighting unit, namely Managing an average rating of 64.3%,Leading an average rating of 69%, and Cognitive an averageassessment of 79%. Proposed developments for eachcompetency unit to increase the value of the project managerwill be planned and implemented several types of learningaccording to the results of weak scores. This type of learning isaccompanied by experts in their respective fields. Keywords — Project Manager, Project Manager CompetencyDevelopment Framework (PMCDF®), Personal Aspect, AHP,Skala Likert, and Development Proposal Plan